Micro‐Nano Porous Structure for Efficient Daytime Radiative Sky Cooling. (19th August 2022) - Liu, Junwei; Tang, Huajie; Jiang, Chongxu; Wu, Shiqiang; Ye, Long; Zhao, Dongliang; Zhou, Zhihua
Abstract: With the aggravation of global warming and extreme weather, cooling demand has witnessed a continuous increase and is expected to increase tenfold by 2050. Radiative sky cooling (RSC) without any pollution and energy consumption has drawn worldwide attention in the past few years. Large‐scale and scalable porous cooling materials have greatly advanced the progress of this technology. Herein, a critical review on porous cooling materials with the goal of advancing their commercial applications is presented. The detailed design principles of daytime radiative cooling are first discussed to clarify the critical factors of porous structures for great cooling performance. What follows are detailed discussions on porous cooling materials from pore‐forming methods. Subsequently, the recent progress of the promising particle‐embedding porous structures, mainly including white and colorful coolers for various applications, is outlined. Additionally, some special cooling materials are highlighted to further broaden the applications of RSC technology. Last but not the least, the remaining open challenges and the insights are presented for the further advance of the commercialization progress. Abstract : Radiative sky cooling without any pollution and energy consumption has drawn worldwide attention in the past few years. A critical review on porous cooling materials, including porous coolers, particle embedding coolers and special coolers, is presented to further advance the commercial applications of radiative cooling technology.